Pengaruh Pendapatan Orang Tua dan Prestasi Belajar Terhadap Minat Melanjutkan Pendidikan ke Perguruan Tinggi Pada Siswa Kelas XII Jurusan IPS SMAN 3 Kota Jambi - Eka Indriani, Novita; Khairinal, Khairinal; Arief, Hidayatul (Edu Sosial, 2023)
: Senior High School is an educational institution that emphasizes the mastery of knowledge that is theoretical in its learning as a provision for continuing education to a higher level (university). But in reality, at this time there are still many high school students who do not continue their education to higher education and prefer to go straight into the world of work. Where this can happen because it is influenced by two factors, namely external factors and internal factors such as parental income and learning achievement. This study aims to determine the effect of parents' income and learning achievement on the interest in continuing their education to tertiary education in class XII students of Social Sciences Department at SMAN 3 Jambi City. This research is a quantitative research with descriptive analysis method. The data collection technique used in this study was using a questionnaire with a total sample of 108 students of class XII Social Sciences Department at SMAN 3 Jambi City. Methods of data analysis using descriptive analysis, normality test, linearity test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple regression test, partial test (t test), simultaneous test (F test) and coefficient of determination test (R2). The results of this study indicate that: There is a significant influence between parents' income on the interest in continuing their education to tertiary education in class XII students of the IPS Department of SMAN 3 Jambi City with a value of tcount > ttable, namely 3.392 > 1.982. Furthermore, there is a significant influence between learning achievement on the interest in continuing their education to tertiary institutions in class XII students of the Social Sciences Department at SMAN 3 Jambi City with a tcount > ttable, namely 4.440 > 1.982. And there is a significant influence between parents' income and learning achievement on the interest in continuing their education to tertiary education in class XII students of the IPS Department of SMAN 3 Jambi City, where the value of Fcount > Ftable is 23.299 > 3.1. From the results of this study it is suggested that students can further improve learning achievement both from the cognitive, affective, and psychomotor domains in order to increase self-confidence to continue their education at a higher level.Keywords: Learning Facilities, Peers, Service quality.